(untitled) (Herald of the National Children’s Medical Center, 2025)
Membranoproliferative glomerulonephritis (MPGN) is often associated with hepatitis C virus infection and an increased risk of thrombosis. However, rare cases of MPGN with manifestations of thrombotic microangiopathy (TMA) without involvement of a viral agent have been reported. The presented clinical case illustrates such an atypical combination of pathology in an adolescent, which requires a special approach to diagnosis and treatment.